A proposed vertical path adjustment factor for dust storm attenuation prediction - Elsheikh, Elfatih A. A.; Islam, Md. Rafiqul; Al-Khateeb, Khalid A. Saeed; Alam, A. H. M. Zahirul; Omer Elshaikh, Zain Elabdin (2011)
In this paper an adjustment factor which reflects the vertical variation of dust storm (earth satellite links) has been derived based on the analysis of the vertical dust storm behavior. The paper has been divided to four parts. First an introduction to the dust storm phenomena and its effect on microwave signal attenuation. Secondly, observations of the behavior of the vertical dust storm intensity variation. Thirdly, the vertical path adjustment factor has been estimated. Lastly, a conclusion summarized the results and recommended further work. It has been found that the predicted attenuation without the vertical path adjustment factor is much higher than with the vertical path adjustment factor. Therefore, the vertical path adjustment factor will provide optimum utilization for the transmission resources.